Research of Permanent Magnet Synchronous Motor Control Stability Improving in Depth Flux-weakening Area - SHI Min; FENG Jiang-hua; XU Junfeng; HE Yaping; XIAO Lei; WEN Yuliang (机车电传动)
Stability problem of PMSM current vector control in depth flux-weakening area was analyzed, and a new flux-weakening control scheme in the MTPV of PMSM was proposed, which significantly improved stability and increased speed range while maintaining maximum possible torque capability with smooth transition between different operation regions. Through MATLAB/Simulink simulation, the correctness of the theoretical analysis was verified; it was shown that PMSM could operate in the speed ratio of 1:4 without any current oscillation and instability with the new scheme.